Toxic epidermal necrolysis - Demenj, Marko (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Toxic epidermal necrolysis (TEN) is a severe cutaneous adverse reaction triggered by various classes of drugs. Clinical manifestations include prodromal symptoms resembling a febrile illness, followed by skin and mucosal lesions. This study presents a series of fatal TEN cases, with a focus on factors that may have influenced mortality, including differential diagnoses, associated comorbidities, treatment choices, and complications of TEN. Methods: Data were collected from electronic medical records of patients hospitalized at a dermatology clinic. Results: Case 1 involved TEN in a 42-year-old female, initially misdiagnosed as mycoplasma-induced rash and mucositis (MIRM), who succumbed to sepsis. Case 2, a 50-year-old female with 80% of her body surface area affected, saw low-dose IVIg treatment prove ineffective, leading to multiorgan failure. Case 3 involved allopurinol-induced TEN in a 53-year-old with Balkan endemic nephropathy, resulting in fatal renal failure. Conclusions: The cases presented highlight potential challenges in differentiating TEN from MIRM in the early stages of TEN. Highdose IVIg is generally recommended, whereas the effectiveness of low-dose IVIg is inconsistent, and it proved insufficient in the case presented, potentially due to the presence of multiple comorbidities. Preexisting conditions such as renal disease significantly influence fatal outcomes in TEN patients.
Keywords: Balkan endemic nephropathy; Balkanska endemična nefropatija; cutaneous adverse reactions; izpuščaj in mukozitis povzročen z mikoplazmo; kožni neželeni učinki; low-dose IVIG; mycoplasma-induced rash and mucositis; nizki odmerki IVIG; toksična epidermalna nekroliza; toxic epidermal necrolysis